Das (Wasted) Kapital : Firm Ownership and Investment Efficiency in China - Dollar, David (IMF Working Papers; Working Paper ;, 2007)
Based on a survey that we designed and that covers a stratified random sample of 12,400 firms in 120 cities in China with firm-level accounting information for 2002-2004, this paper examines the presence of systematic distortions in capital allocation that result in uneven marginal returns to capital across firm ownership, regions, and sectors. It provides a systematic comparison of investment efficiency among wholly and partially state-owned, wholly and partially foreignowned, and domestic privately owned firms, conditioning on their sector, location, and size characteristics. It finds that even after a quarter-of-century of reforms, state-owned firms still have significantly lower returns to capital, on average, than domestic private or foreign-owned firms. Similarly, certain regions and sectors have consistently lower returns to capital than other regions and sectors. By our calculation, if China succeeds in allocating its capital more efficiently, it could reduce its investment intensity by 5 percent of GDP without sacrificing its economic growth (and hence deliver a greater improvement to its citizens' living standard).